Spiritual mentoring : a guide for seeking and giving direction - Anderson, Keith, 1949-; Reese, Randy D. (Downers Grove, Ill IVP Books, 1999)
Spiritual mentoring is not only for pastors or saints. Mentors are ordinary Christians who are willing to enter into a faith relationship with another person who wants to grow. Likewise, those who are mentored are not seminary candidates but simply followers of Jesus who long for guidance in their spiritual journey.
In this book Anderson and Reese show you how to mentor and be mentored as they introduce, chapter by chapter, the work of a different classical spiritual writer, including: *Augustine * Aelred of Rievaulx *John of the Cross *Julian of Norwich * Ignatius of Loyola *Teresa of Avila *Madame Jeanne Guyon.
These writers offer timeless insights from centuries past, while Anderson and Reese help you put their teaching into practice today to grow closer to Jesus in the company of another believer. If you want to learn how to help younger Christians grow while stretching your own faith, or if you want to tap into the experience of a Christian friend who is farther along the road of faith, this is the book that will get you started.
An imitative faith -- Reading between the lines : what is spiritual mentoring? -- The art of beginning well : attraction --
Includes bibliographical references (pages 183-191).
Keywords: Spiritual direction